(untitled) (Journal of Plant Disease Sciences, 2018)
Turmeric (Curcuma longa) is a tropical crop grown in India, occupies the third position in its importance among spice crops and native to tropical South East Asia. The economic importance of turmeric is the dried rhizome. India has a 232.6 thousands ha area under turmeric cultivation with total production of 1189.90 thousand tons and productivity is 51.15q/ha (Anonymous (2014)). Turmeric crop is highly prone to several fungal diseases (Purthi, 2000). The serious foliar diseases reported in Uttar Pradesh are leaf spot caused by Colletotrichum capsici (Syd.) Butler & Bisby, and leaf blotch caused by Taphrina maculans, Butler. Despite the importance of the crop farmers fail to realize maximum potential yields because of several limiting factors, among them low yielding with foliar disease susceptible variety are one of the main region. Therefore aims of present work are evaluation and identification of genotypes for foliar disease resistance and quality yield of turmeric.